Application of Perinatal Derivatives in Ovarian Diseases - Lange-Consiglio, Anna; Capra, Emanuele; Herrera, Valentina; Lang-Olip, Ingrid; Ponsaerts, Peter; Cremonesi, Fausto (Frontiers in Bioengineering and Biotechnology, 2022)
Reproductive diseases could lead to infertility and have implications for overall health, most importantly due to psychological, medical and socio-economic consequences for individuals and society. Furthermore, economical losses also occur in animal husbandry. In both human and veterinary medicine, hormonal, and surgical treatments, as well as assisted reproductive technologies are used to cure reproductive disorders, however they do not improve fertility. With ovarian disorders being the main reproductive pathology in human and bovine, over the past two decades research has approached regenerative medicine in animal model to restore normal function. Ovarian pathologies are characterized by granulosa cell and oocyte apoptosis, follicular atresia, decrease in oocyte quality and embryonic development potential, oxidative stress and mitochondrial abnormalities, ultimately leading to a decrease in fertility. At current, application of mesenchymal stromal cells or derivatives thereof represents a valid strategy for regenerative purposes. Considering their paracrine / autocrine mode of actions that are able to regenerate injured tissues, trophic support, preventing apoptosis and fibrosis, promoting angiogenesis, stimulating the function and differentiation of endogenous stem cells and even reducing the immune response, are all important players in their future therapeutic success. Nevertheless, obtaining mesenchymal stromal cells (MSC) from adult tissues requires invasive procedures and implicates decreased cell proliferation and a reduced differentiation capacity with age. Alternatively, the use of embryonic stem cells as source of cellular therapeutic encountered several ethical concerns, as well as the risk of teratoma formation. Therefore, several studies have recently focussed on perinatal derivatives (PnD) that can be collected non-invasively and, most importantly, display similar characteristics in terms of regenerating-inducing properties, immune-modulating properties and hypo-immunogenicity. This review will provide an overview of the current knowledge and future perspectives of PnD application in the treatment of ovarian hypofunction.